Ask a Question

8x-(2x+1)=3x-13

+4 votes
8x-(2x+1)=3x-13 precalc
asked Sep 11, 2013 in Calculus by R.custer Newbie (120 points)
   

1 Answer

+3 votes
8x - (2x + 1) = 3x - 13 (simplify by removing the parenthesis)

8x - 2x -1 = 3x - 13 (subtract the 2x from the 8x and add 1 to both sides of the equation)

6x = 3x - 12 (subtract 3x from both sides of the equation)

3x = -12 (divide both sides by 3)

x = -4
answered Sep 11, 2013 by stg1.stewart Inquisitive Expert (21,460 points)

Categories

ExplainPlease on Facebook

75,014 questions

48,874 answers

1,169 comments

87,152 users

CuriousGirl313,480
BobTheAnswerGuy310,070
smartguy111,120
charlie100,740
bbrown97,580
answerwiz94,860
The.Sage93,460
amanda0192,460
kfox83,500
lsmith82,840
...